Optimization of Protein Hydrolysate from Earthworms (Perionyx excavatus) of Angiotensin-I-Converting Enzyme Inhibitory Activity by One Variable at a Time - Bui, Phong Thanh; Hoang, Truc Anh; Pham, My Thi Thuy; Tran, Linh Le Phuong; Nguyen, Oanh Kim (Universitas Gadjah Mada, 2025)
Hypertension, characterized by elevated blood pressure, is commonly treated with angiotensin-I-converting enzyme (ACE) inhibitors. This study evaluated the ACE inhibitory activity (ACEIA) of protein hydrolysate from earthworms (Perionyx excavatus) by commercial proteases. The results showed that the protein hydrolysate of earthworms gave the highest ACEIA of 85.38 ± 2.31% (at the protein concentration of 2 mg/mL) and IC50 value of 844.64 μg/mL when the earthworms were hydrolyzed with Flavourzyme® 500 MG under optimized conditions such as earthworm:phosphate buffer ratio of 1:6 (w/v), hydrolysis temperature of 50 °C, pH 7, enzyme:substrate ratio of 600 U/g protein and hydrolysis time of 2 h. The membrane further fractionated the hydrolysate, and the < 1 kDa fraction had the highest ACEIA with an IC50 value of 261.94 μg/mL. The stability of ACEIA was assessed under various conditions, including in vitro digestion, heat treatment at 100 °C for 180 min, and pH adjustments from pH 1 to 11. The < 1 kDa fraction maintained ACEIA activity at 133.34, 76.25, and 84.95%, respectively, after these treatments. These results suggest that earthworm protein hydrolysates, particularly the <1 kDa fraction, exhibit strong stability and could be promising candidates for the development of functional foods or pharmaceuticals targeting hypertension.